Airflow Cooling Mechanism for High Power-Density Permanent Magnet Motor - Awungabeh Flavis Akawung; Besong John Ebot; Yasutaka Fujimoto (IEEE Open Journal of the Industrial Electronics Society)
High power-density electric machines present the benefits of high torque and speed. However, this generally comes with heating problems characterized by high temperatures that affect performance. Conventional approaches to address overheating are to include cooling fans or jackets within the stator core of the machine. This approach is challenging to implement in small-size high power-density machines. In this article, a cooling mechanism integrated in the rotor of a high power-density permanent magnet motor is proposed. It comprises a set of six holes, shrouded within a hollow shaft. The mechanism is based on conditioning air due to a centrifugal force that is produced by the rotational speed of the rotor from the inlet. A theoretical model based on flow resistance network is proposed to analyze the airflow rate. An analytical thermal model based on lumped parameter thermal network is developed to analyze the effect of the flow rate on the temperature distribution in the motor. Also, a simulation analysis model was conducted using computational fluid dynamics to analyze the effect of air flowing in the motor. An experimental prototype is developed to verify, validate, and evaluate the proposed cooling model. The cooling system is effective in reducing temperatures from speeds above 6000 min−1.